(untitled) (Quinto Sol, 2020)
This article examines –based on Uruguayan, US and Argentinean diplomatic documents– the controversy aroused in the American countries by the “proposal of multilateral intervention” of the Uruguayan Ministry of Foreign Affairs, Eduardo Rodríguez Larreta in November, 1945. The Department of State of the United States, participated in the incubation of this doctrine, as their defenders sponsored it. This was in fact what his contemporaries suspected, and the primary sources consulted for this work, verify that intuition. Moreover, the proposal was considered against Farrell’s and Peron’s dictatorship, which is somewhat true. This undertaking violated the “sacred” principle of non-intervention and put into consideration the exchange of views to make actions in those countries whose regimes violated the essential human rights, even if those countries did not commit external aggressions or direct threats against the international peace. This research illustrates how Larreta’s doctrine was another link in the process of the US involvement in the Argentinean electoral campaign of 1946 with the aim of curbing the nascent Peronism.